2020
DOI: 10.1002/nop2.457
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role‐based challenges of providing culturally inclusive health care for maternal and child health nurses: Qualitative findings

Abstract: Aims To explore how maternal and child health nurses (MCHNs) working in a specific regionally located service perceive and experience delivering health care to a diverse population. Design Qualitative exploratory study. Methods Qualitative interviews were conducted with MCHNs (N = 6) working in a particular regionally located service. Data were selectively coded, categorized and interpreted through a process of argument writing influenced by poststructuralist thought and Foucauldian conceptualizations of power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Addressing power in interpersonal relationships is at the core of cultural safety (Malatzky et al 2020). In this review, strong relationships were fundamental to quality care for vulnerable Aboriginal families.…”
Section: Relationshipsmentioning
confidence: 98%
“…Addressing power in interpersonal relationships is at the core of cultural safety (Malatzky et al 2020). In this review, strong relationships were fundamental to quality care for vulnerable Aboriginal families.…”
Section: Relationshipsmentioning
confidence: 98%
“…It was clear throughout the interview transcripts that these statements were not based on discussions they have had with their clients, but on assumptions made about the limitations of many non-Australian health care systems. In doing so, health professionals deny how their own practice is itself culturally constructed and privileged (Malatzky et al, 2020). This microaggression reinforces an assumption of a user's lack of knowledge of the service by blaming the lack of services in a client's country of origin.…”
Section: Expression Of Cultural Superioritymentioning
confidence: 99%
“…Dr. James Marion Sims, known as the father of gynecology, made advancements in the field by operating on enslaved Black people without their consent and anesthesia [17]. Maternity care sits within a healthcare system shaped by a white, western-based model [18]. This model privileges some (white, middle-upper class) while perpetuating harm to others by not providing a culturally safe and inclusive care environment for all patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…Maternity care sits within a healthcare system shaped by a white, western-based model [18]. This model privileges some (white, middle-upper class) while perpetuating harm to others by not providing a culturally safe and inclusive care environment for all patients [18]. A national study examining racial diversity in Obstetrician and Gynecologist (OBGYN) residency and fellowship programs found that from 2012 to 2018, over half (54.2%) of OBGYN residents were white [19].…”
Section: Introductionmentioning
confidence: 99%